Effects Nutrient Additives of NPK Fertilizer and Coconut Water on the Yield of White Oyster Mushroom (Pleurotus ostreatus) - Alfarizi, Muhammad Salman; Gusmawartati, Gusmawartati; Zulfatri, Zulfatri (UNIVERSITY OF LAMPUNG, 2022)
White oyster mushroom (Pleurotus ostreatus) requires a source of nutrients for growth and development. The provision of NPK fertilizer aims to increase the source of media nutrients so that the results obtained are better in quantity and quality. Growth regulators can stimulate the relatively long growth of oyster mushroom mycelium. Growth regulators contain hormones that can support growth rates. One alternative natural growth regulator that can be used is coconut water. The research was carried out at the oyster mushroom kumbung at Pekanbaru, using a completely randomized design, consisting of 2 factors and three replications. The first factor was NPK fertilizer consisting of 4 levels (0, 7.5, 10, 12.5) g per baglog. The second factor was coconut water consisting of 4 levels (0, 3, 6, 9) ml per baglog. Data were analyzed using Analysis of Variance and further tested using DNMRT level 5%. The results showed that adding 10 g of NPK fertilizer and 6 ml of coconut water per baglog was a better dose for the number of fruit bodies, fresh fruit body weight, fruit cap diameter, fruit stalk length, and biological efficiency.